Treatment of brilliant blue FCF using gas-liquid phase reactor by pulse power technology - Mobarra, Mohammadjavad (2013)
Currently the harm effects of wastewater from industrial sectors to the environment become one of public major concern. There are several wastewater treatment methods and techniques which have been introduced by using biological, chemical, and physical process. However, it is found that there are some shortcomings in the current available methods and techniques. For instance application of chlorine can cause bacterial disinfection of water but still this method produce secondary harmful carcinogenic disinfection by-product and application of ozone treatment which is one of the most reliable technique need to improve due to production of ozone and treatment system. In order to obtain a better understanding in wastewater treatment processing, a study to improve the wastewater treatment system and hybrid discharge reactor to acquire gas-liquid phase corona like discharge is accomplished. Furthermore, design and development of frequency controller which will be applied to Blumlein pulse power generator is accomplished. In this experiment pulse power technology used to generate a high voltage pulses in a very short range of time such as nano second and micro second. Also pulse width modulation circuit helps to control and obtain an ideal frequency for a direct current motor to gain better efficiency in terms of output pulse. Hybrid Discharge reactor designed to obtain a gas-liquid phase Therefore Spark discharge in liquid is benefit to treat contaminant extra completely than corona discharge. The Hybrid Discharge reactor could produce both spark discharge in gas phase and liquid phase (sparkspark discharge). Though separately after hydrogen radicals it is shown that oxygen (typical shape of oxygen OI) as well as ultraviolet high each yield through the actual release performs a good essential part within often the treatment and also reactive species especially and electric conductivity increase dramatically in terms of parameter of waste water unlike PH and temperature.